Character Development through Flag Ceremony and Marching Regulations Courses: Insight from the Physical Education Program at Jenderal Soedirman University - Wahono, Bayu Suko (Indonesian Research Journal on Education, 2024)
Recently, character education is considered essential for students due to a crisis of character among them. This situation has led to the emergence of various programs designed to rebuild student character, one of which is through the course on flag ceremonies and marching regulations (TUB and PBB). This study seeks to identify the character traits that emerge in students following their completion of the TUB and PBB courses within the Physical Education program at Jenderal Soedirman University. The research uses a qualitative approach with a case study type. The selection of subjects was done through purposive sampling techniques. Data collection techniques include observation, interviews, and documentation. Data analysis was performed using the descriptive data analysis model by Miles and Huberman. To ensure data validity, source and technique triangulation were used. The results of the study show that the character traits developed in students after participating in the TUB and PBB course are cooperation, discipline, leadership, and responsibility.